2013
DOI: 10.1007/s10059-013-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-Rich Repeat-Containing G-Protein Coupled Receptor 5/GPR49 Activates G12/13-Rho GTPase Pathway

Abstract: Leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5/GPR49) is highly expressed in adult stem cells of various tissues, such as intestine, hair follicles, and stomach.LGR5 is also overexpressed in some colon and ovarian tumors. Recent reports show that R-spondin (RSPO) family ligands bind to and activate LGR5, enhancing canonical Wnt signaling via the interaction with LRP5/6 and Frizzled. The identity of heterotrimeric G-proteins coupled to LGR5, however, remains unclear. Here, we show that Rho GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…In addition to the 7-TM bundle, Lgr5 contains canonical “DRY”, “NPXXY”, and “SSS” serine cluster motifs (Figure 1 and Figure 2). Moreover, during review of our manuscript, a single report was published indicating that Lgr5 may couple to the heterotrimeric G protein alpha subunits G 12/13 [54]. Therefore, these recent data, together with the multiple lines of structural, biochemical, and cell biological evidence that we present here, indicate that Lgr5 possesses the capacity for classical GPCR behavior.…”
Section: Discussionsupporting
confidence: 61%
“…In addition to the 7-TM bundle, Lgr5 contains canonical “DRY”, “NPXXY”, and “SSS” serine cluster motifs (Figure 1 and Figure 2). Moreover, during review of our manuscript, a single report was published indicating that Lgr5 may couple to the heterotrimeric G protein alpha subunits G 12/13 [54]. Therefore, these recent data, together with the multiple lines of structural, biochemical, and cell biological evidence that we present here, indicate that Lgr5 possesses the capacity for classical GPCR behavior.…”
Section: Discussionsupporting
confidence: 61%
“…So far, no direct evidence indicates that the RSPO proteins regulate the cAMP-PKA-ATF4 pathway through the LGR4 receptor. Recently, it was also demonstrated that overexpression of the LGR5 receptor induced the G 12/13 -Rho GTPase pathway independently of RSPOs (45). Therefore, future investigation of whether the deficits in myogenic differentiation observed in Lgr4-KD cells is also linked to the disruption of the RSPO-independent GPCR pathway is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, C3 was studied in cell division and apoptosis [80,81]. In more recent studies C3 was used to delineate the signaling induced by adiponectin [82], leptin [83], and the G protein-coupled receptor GPR49 [84].…”
Section: C3-like Adp-ribosyltransferasesmentioning
confidence: 99%